Prediction Analysis of Profitability and Liquidity Levels at PT. Bank Rakyat Indonesia Syariah Tbk - Martha Suhardiyah; Siti Istikoroh; Yuni Sukandani (Jurnal Multidisiplin Madani, 2023)
This research aims to determine and predict the level of profitability and liquidity at PT. Bank Rakyat Indonesia Syariah Tbk, . The type of research used is descriptive quantitative research to explain the soundness level of banks, to analyze trends in soundness, banks use the least square method. As a population is the Annual report of PT. Bank Syariah Indonesia Tbk, .2016-2020 period, with withdrawal techniques. sample using purposive sampling) with the criteria of having an annual report with a ratio, ROA, and liquidity. Data analysis, from this study shows that the trend of PT BRI Syariah (PT. Bank Rakyat Indonesia Syariah Tbk) in 2021-2025 for profitability as measured by the ROA ratio tends to decrease but is still in the criteria of being quite healthy, while in terms of liquidity in 2021 there is increase, in 2022-2025 it tends to be stable in criterion 1 very healthy